Galleria mellonella Larvae as a Model for Investigating Fungal—Host Interactions - Curtis, Aaron; Binder, Ulrike; Kavanagh, Kevin (Frontiers in Fungal Biology, 2022)
Galleria mellonella larvae have become a widely accepted and utilised infection model due to the functional homology displayed between their immune response to infection and that observed in the mammalian innate immune response. Due to these similarities comparable results to murine studies can be obtained using G. mellonella larvae in assessing the virulence of fungal pathogens and the in vivo toxicity or efficacy of anti-fungal agents. This coupled with their low cost, rapid generation of results and lack of ethical/legal considerations make this model very attractive for analysis of host-pathogen interactions. The larvae of G. mellonella have successfully been utilised to analyse various fungal virulence factors including toxin and enzyme production in vivo providing in depth analysis of the processes involved in the establishment and progression of fungal pathogens (e.g. Candida spps, Aspergillus spp., Madurella mycetomatis, Mucormycetes and Cryptococcus neoformans). A variety of experimental endpoints can be employed including analysis of fungal burdens, alterations in haemocyte density or sub-populations, melanisation and characterisation of infection progression using proteomic, histological or imaging techniques. Proteomic analysis can provide insights into both sides of the host-pathogen interaction with each respective proteome being analysed independently following infection and extraction of haemolymph from the larvae. G. mellonella can also be employed for assessing the efficacy and toxicity of antifungal strategies at concentrations comparable to those used in mammals allowing for early stage investigation of novel compounds and combinations of established therapeutic agents. These numerous applications validate the model for examination of fungal infection and development of therapeutic approaches in vivo in compliance with the need to reduce animal models in biological research.